Magnetic Ions in Crystals. - Stevens, K. W. (Princeton University Press, 2014)
There have been many demonstrations, particularly for magnetic impurity ions in crystals, that spin-Hamiltonians are able to account for a wide range of experimental results in terms of much smaller numbers of parameters. Yet they were originally derived from crystal field theory, which contains a logical flaw; electrons on the magnetic ions are distinguished from those on the ligands. Thus there is a challenge: to replace crystal field theory with one of equal or greater predictive power that is based on a surer footing. The theory developed in this book begins with a generic Hamiltonian,
Keywords: Magnetic ions.; Crystal field theory.; Hamiltonian systems.; Ions magnétiques.; Théorie du champ cristallin.; Systèmes hamiltoniens.; SCIENCE -- Physics -- General.; SCIENCE -- Energy.; SCIENCE -- Mechanics -- General.; Crystal field theory; Hamiltonian systems; Magnetic ions